"I had a dream: it was to play the games". Sports socialisation processes of French paralympic athletes. Issue 2 (3rd April 2022) - Richard, Remi; Burlot, Fabrice; Duquesne, Valentine; Joncheray, Helene
Abstract: In this article, we provide a diachronic and synchronic study of the socialisation processes that contribute to participation in Paralympic Games. We will focus both on the socializations that were involved in the engagement in elite sports practice, and on the socializations that took place during the preparation for the 2016 Rio Paralympic Games. Thirteen athletes who took part in the Rio Paralympic Games were interviewed. Beyond the diversity of the sports socialisation experiences of French athletes who participated in the Paralympic Games, this article also highlights similarities: the results highlight i) the importance of early socialisation to sport practice; ii) that commitment in high-performance paralympic sport is determined by a very rapid progression in the athletes' performances; iii) the essential role of family as an emotional, financial and organisational support. These results reveal social levers and brakes to the optimisation of Paralympic performance, and in this sense can be used to guide the accompaniment of athletes by Paralympic institutions.